Prosthetic mitral valve Aspergillus fumigatus endocarditis. (2020) - Museedi, Abdulrahman S.; Nashawi, Mouhamed; Ghali, Abdullah; Alshami, Abbas; Chakravorty, Ripa
Abstract: Aspergillus endocarditis is a fatal source of valvular infection with a near 100 % mortality rate if pharmacotherapy and valve-replacement surgery are not initiated swiftly after diagnosis. Complicating its diagnosis is the low yield for growth on standard blood culture and time requirements for molecular diagnostic tools to return a result. Aspergillus endocarditis of the mitral valve presents as valvular vegetations that reduce the caliber of the mitral valve and can cause syncope as in the case of mitral stenosis with subsequent valve failure, left atrial enlargement, and prospective cardiovascular failure. Reports of the management of Aspergillus endocarditis after serial mitral valve replacement are not prominent in the literature. We report the case of a 41-year-old female with previous mitral valve prosthesis who received a second prosthetic mitral valve after a syncopal episode. Vegetations resembling thrombi were noted on transesophageal echocardiogram, diagnosed as Aspergillus fumigatus endocarditis, and successfully treated with antifungal therapy in conjunction with removal of her dysfunctional prosthesis.